The performance of low crested breakwaters as a sand trap for shore protection. Issue 1 (February 2020) - Munandar, Fikri Aris; Triatmadja, Radianta; Yuwono, Nur
Abstract: The low crested breakwater (LCB) is considered as a new coastal protective structure which has not been widely used compared to other coastal protection structures. LCB has more advantages than conventional ones such as breakwaters, requiring lower cost and aesthetically not disturbing nature because of its position which is below sea level so it is suitable for beach tourism. Studies on low crested breakwaters are mostly about the ability to absorb energy waves and how beach responded to the structure. However, the study on the ability of this low crested breakwater such as a sand trip is still limited. Therefore, this study aims to observe the breakwater's performance as a sand trap for shore protection and the effect of the parameters on the performance. This study was conducted on the plexiglass wave made with a length of 18 m, a width of 0.3 m and a depth of 0.45 m. Wave parameters (height and period) and structure parameters (height and width) were employed as a reference in this study. This research was conducted by varying the waves, height and water depth. The results indicate that the number of transport sediment tends to be increased following the wave height (Hi), the water depth at the height of the structure (Rc) and reduced wavelength (L). The type and position of a wave breaking also affect the amount of transport sediment.